SYNTHESIS OF SILVER NANOPARTICLES USING CHEMICAL REDUCTOR: MINI REVIEW - Az Zahra, Upi Fathimah; Panggabean, Aman Sentosa; Hindryawati, Noor (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Silver nanoparticles are particles whose range ranges from 1-100 nm. Formation of metal nanoparticles can be done by top down (physics) and bottom up (chemistry) methods. Chemical reduction is a very commonly used method because it is relatively simple, easy and effective to produce AgNPs. Synthesis of silver nanoparticles was carried out by forming a colloidal silver solution using the silver nitrate reduction method with a chemical reducing agent. Some chemical reducing agents that can be used are ascorbic acid, citric acid, hydrazine and NaBH4. In addition, a stabilizing agent is needed to prevent agglomeration of the formed nanoparticles. The purpose of this article review is to determine the characteristics of silver nanoparticles synthesized using chemical reducing agents based on UV-Vis, PSA, TEM and SEM spectrophotometer data. The method used is the method of literature review. The results show that the synthesis of silver nanoparticles by reducing silver nitrate with sodium borohydride and poly acrylic acid (PAA) stabilizer produces an average size of 71.8 nm silver particles, the PVP stabilizer produces an average size of 96.0 nm silver particles, synthesis of silver nanoparticles using reducing agents ethylene glycol and polyvinylpyrrolidone (PVP) produces an average size of silver particles of less than 10 nm, synthesis of silver nanoparticles using reducing agents hydrazine hydrate and polyvinyl alcohol produces an average size of silver particles of 10-60 nm. Keywords: silver nanoparticle, NaBH4, stabilizer